Pharmacists' Opinions on the Implementation of HIV and HepC Point-of-Care-Testing in a U.S. Pharmacy Chain - Elizabeth So; Monica Brands; Erin Suomala; Bridget Ogden; Jennifer Riss; Alina Cernasev; Jon Schommer (University of Minnesota Libraries Publishing, 2019)
Background: The role of community pharmacists continues to expand with immunizations, medication therapy management, and point-of-care testing (POCT). Current guidelines recommend that Human Immunodeficiency Virus (HIV) and Hepatitis C (HCV) testing become integrated into routine care. Current guidelines recommend all people aged 13-64 be tested for HIV at least once in their lifetime, with those at higher risk for HIV tested at least annually.1 Regarding HCV, current guidelines recommend a one-time HCV test in persons born from 1945 to 1965, as well as other individuals based on exposures, behaviors, and conditions or circumstances that increase HCV infection risk.2 Currently available HIV and HCV treatment regimens are safe and highly effective. With HCV, successful treatment can halt disease progression to cirrhosis, end-stage liver disease, and hepatocellular carcinoma.3 POCT in community pharmacy offers an ideal location due to its accessibility, convenience, and lower cost to patients who might not otherwise be tested. However, HIV and HCV screenings are not routinely conducted by community pharmacists due to many barriers. Though many barriers to HIV and HCV POCT have been identified at the patient, provider, and institutional level, little is known about pharmacist-perceived barriers. It is worth noting that the barrier of state legislation limiting POCT in pharmacies has been resolved - currently 49 states have some form of statute that allows for delegation of prescriptive authority between a prescriber and community pharmacist.4 Though this removed barrier means increased availability of POCT, as the studies above have demonstrated, the mere availability of POCT is not enough for its implementation. Objective: The main objective of this study is to identify pharmacist-perceived barriers and their level of confidence in performing community pharmacy-based POCT for HIV and HCV. Methods: A cross-sectional survey was sent to all pharmacists working in a regional grocery store chain to evaluate their opinions and attitudes toward the implementation of POCT for HIV and HCV. The electronic survey questions consisted of Likert scale, select-all-that-apply, yes/no and no open-ended questions. Results: The perceived barriers to implementation of HIV and HCV POCT in a community setting identified by pharmacists include staffing, time to conduct test, patient out-of-pocket cost, and discussion of positive results. Pharmacists' perceived level of confidence was greatest with providing basic education and incorporating HIV and HCV POCT into workflow; whereas discussion of a positive result was perceived as less confident.  Conclusions: While this survey determined pharmacist support for the implementation of HIV and HCV POCT, additional studies are needed before effective implementation of HIV and HCV POCT in a community pharmacy chain.   Article Type: Original Research